RESISTANCE OF KATOBENGKE ETHNIC PEOPLE TO HEGEMONY OF TRADITIONAL ELITES IN BAUBAU CITY SOUTH EAST SULAWESI - Dirman, La Ode; Kumbara, A.A. Ngurah Anom; Mbete, Aron Meko; Mudanu, I Gede Mudana (E-Journal of Cultural Studies, 2015)
The Katobengke ethnic group is one of the sub Buton ethnic groups which has been marginalized since the new order. When the reformation era started, they resisted the system of the knowledge which the traditional elites had. This present study was intended to understand the practice of resistance shown by the Katobengke people to the hegemony of the traditional elites based on the historical history and its implication on themselves and the traditional elites. It can be theoretically used as a model and a new concept and method of the development of the cultural studies. It can practically give input to the government as to the empowerment of the marginalized people using their local genius and maintenance of their cultural identity. The result of the present study shows that the resistance shown by the Katobengke people to the traditional elites through the mythological discourse of identity; symbolic resistance and physical violence; the factors contributing to the resistance were discrimination of identity, stigmatization of the Indonesian Communist Party ‘Partai Komunis Indonesia (PKI), the slave stereotype, the traditional taboo; the implication of the resistance is that the sultanate ideology was ineffective any longer to the Katobengke people’s interest, the appearance of new stratification, resistance to the traditional stereotype and taboo, the change in traditional costume, La Ode was used as the title, change in profession from becoming farmers into working as providers of services, and spirituality were used for political communication.
Keywords: hegemony, counter hegemony, stereotype, and traditional taboo.